A visualization method for probing grain boundaries of single layer graphene via molecular beam epitaxy. (6th July 2017) - Zhan, Linjie; Wan, Wen; Zhu, Zhenwei; Zhao, Zhijuan; Zhang, Zhenhan; Shih, Tien-Mo; Cai, Weiwei
Abstract: Graphene, a member of layered two-dimensional (2D) materials, possesses high carrier mobility, mechanical flexibility, and optical transparency, as well as enjoying a wide range of promising applications in electronics. Adopting the chemical vaporization deposition method, the majority of investigators have ubiquitously grown single layer graphene (SLG), which inevitably involves polycrystalline properties. Here we demonstrate a simple method for the direct visualization of arbitrarily large-size SLG domains by synthesizing one-hundred-nm-scale MoS2 single crystals via a high-vacuum molecular beam epitaxy process. The present study based on epitaxial growth provides a guide for probing the grain boundaries of various 2D materials and implements higher potentials for the next-generation electronic devices.